American Indian Business : Principles and Practices - Kennedy, Deanna M. (Book collections on Project MUSE., 2017)
"Although there are business programs at nearly 40 tribal colleges and universities, and courses focused on American Indian business practices at additional institutions, no reader or textbook exists for use in these courses. The editors of and co-authors of this proposed volume seek to help business school graduates work more effectively both with and within American Indian communities. Taken together, the essays will help create greater awareness of tribal economies and organizations and their relationship with the dominant culture, facilitate cross-cultural dialogue and understanding, and build public policies that enhance economic self-sufficiency and cultural integrity. Chapters include the following: history of American Indian business; economic sustainability, self-determination, and sovereignty; organization and management; marketing; leadership; human resource management; tribal finance; business strategy; American Indian business law; tribal gaming operations; economic development; entrepreneurship; technology and data management; business ethics; service management; taxation; accounting; and healthcare management."--Provided by publisher